PENGEMBANGAN MULTIMEDIA PEMBELAJARAN SOSIOLOGI UNTUK PEROLEHAN BELAJAR KONSEP PERILAKU MENYIMPANG MENGGUNAKAN PROBLEM BASED LEARNING - Imas Maslahat; HM Asrori; Indri Astuti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractThis Research conducted in SMA Negeri 10 Pontianak aimed to produced several thinks as follows : (1) Find the multimedia profile storyboard which is relevant to the sociology learning for learning concept acquisition of deviant behavior by using problem based learning.  (2) Implemented the procedures of  multimedia  development in sociology learning deviant behavior material by using problem based learning. (3) Achieved the prescription of student’s  learning tasks through sociology learning multimedia deviant behavior material by using problem based learning. (4) Describe the learning concept acquisition of deviant behavior material through problem based learning. This research is a development type (Research and depelovment) by qualitative descriptive approach. The subject of the research was students of X grade SMA Negeri 10 Pontianak. The results of this research are : 1) Image of the multimedia profile storyboard which is relevant to sociology learning that gave the students convenience in understanding and increasing the learning concept acquisition of deviant behavior in M.S. Power format equipped by narration, audio, video and hyperlink; 2) Find the procedures of sociology learning multimedia deviant behavior  material by using problem based learning. 3) Find the image of learning tasks through multimedia and 4)  Students are able to achieved the final purpose in learning that is learning  concept acquisition. To achieved the study result, evaluation and asseesment are performed which is a follow-up or the way to measure the level of students’ mastery.Keywords : Development, Multimedia, Learning Concept Acquisition, Deviant Behavior